HUBUNGAN PERAN KADER POSYANDU DENGAN STUNTING DI DESA SUKOREJO - Sarwoko .; Titik Anggraeni; Ratih Kumala Dewi (STIKES Estu Utomo, 2024)
RELATIONSHIP BETWEEN POSYANDU CADRES AND STUNTING IN SUKOREJO VILLAGE Abstract Stunting is a serious public health issue, particularly in rural areas such as Sukorejo Village. This study aims to explore the relationship between the role of Posyandu cadres and the incidence of stunting in Sukorejo Village. The research method used is an observational study with a quantitative approach. Data were collected through questionnaires and KMS Balita. The results showed a total of 42 cadres and 261 children. The roles of the cadres included providing additional food (60%), educating parents of children (30%), and coordinating with health personnel (10%). Most children did not experience stunting (85.82%), had a risk of stunting (13.03%), and were stunted (1.15%). Data analysis using the Chi-Square test (df=1, p=0.003 < ?=0.05) showed a significant relationship between the role of Posyandu cadres and the incidence of stunting in Sukorejo Village.